Learning language or understanding culture? Discussions about the objectives of including the Chinese language in the state school of Rio de Janeiro - Xie, Jinyu (Revista Letras Raras, 2024)
In recent years, we have witnessed the expansion of Chinese language teaching not only in higher education institutions in Brazil with the establishment of Confucius Institutes, but also through the initiatives of several municipal and state governments that seek to offer the public a multilingual education. In the specific case of the state of Rio de Janeiro, the Joaquim Gomes de Sousa State Mathematics School – Intercultural Brazil-China was created in 2015, through a partnership between the State of Rio de Janeiro and the Hebei Normal University (China). Based on the documentary study and interviews, we intend to discuss how the high expectations of Chinese teachers regarding the linguistic proficiency of their students clash with the Brazilian reality, and how agents of the two nationalities negotiate and adapt to create more realistic objectives in relation to the teaching of Chinese language and culture within a state school. It is necessary not only to have a greater understanding between the two educational cultures, but also a joint effort between teachers, managers and formulators of linguistic and educational public policies to bring about a language-culture education that makes sense to students in the public school system in Brazil. KEYWORDS: ; ;; .